Recent developments in capillary and microchip electroseparations of peptides (2017-mid 2019) - Kašička, Václav (Electrophoresis, 2020)
The review presents a comprehensive survey of recent developments and applications of high performance capillary and microchip electroseparation methods (zone electrophoresis, isotachophoresis, isoelectric focusing, affinity electrophoresis, electrokinetic chromatography, and electrochromatography) for analysis, micropreparation, and physicochemical and biochemical characterization of peptides since 2017 up to about the middle of 2019. Progress in the study of electromigration properties of peptides and in the methodology of their analysis (sample preseparation, preconcentration and derivatization, adsorption suppression, EOF control, and detection) are described. Advances in CE and CEC methods are demonstrated and their applications in the following areas are presented: qualitative and quantitative analysis, determination in complex (bio)matrices, monitoring of chemical and enzymatical reactions and physical changes, amino acid, sequence and chiral analysis, and peptide mapping of proteins. In addition, micropreparative separations and determinations of important physicochemical characteristics of peptides by CE and CEC methods are reported.
Keywords: Peptide Mapping; Capillary Electrochromatography; peptidové mapování; peptidy; proteiny; Electrophoresis, Capillary; Peptides; kapilární elektrochromatografie; elektroforéza kapilární; Proteins